A protocol to visualize on-target specific drug binding in mammalian tissue with cellular resolution using tissue clearing and click chemistry - Zhengyuan Pang; Li Ye (STAR Protocols, 2022)
Summary: Here, we provide a protocol to visualize on-target specific drug binding in mammalian tissue with cellular resolution. By combining tissue clearing and click chemistry, this protocol allows fluorescence tagging of covalent drug binding in situ. In addition, the protocol is compatible with molecular marker staining for cell type identifications.For complete details on the use and execution of this protocol, please refer to Pang et al. (2022). : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.